2019
DOI: 10.1016/j.ejor.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Solving urban transit route design problem using selection hyper-heuristics

Abstract: The urban transit routing problem (UTRP) focuses on finding efficient travelling routes for vehicles in a public transportation system. It is one of the most significant problems faced by transit planners and city authorities throughout the world. This problem belongs to the class of difficult combinatorial problems, whose optimal solution is hard to find with the complexity that arises from the large search space, and the number of constraints imposed in constructing the solution. Hyper-heuristics have emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 47 publications
4
64
3
10
Order By: Relevance
“…In this method, the routes are generated based on the shortest paths searching between OD pairs, and another procedure dealing with constraints is usually needed. For example, the construction and repair procedures used by Ahmed et al [35] and Szeto and Jiang [36], the initial solution generation procedure based on greedy algorithm used by Nikolić and Teodorović [24] and Nayeem et al [37], and the Floyd's algorithm and feasibility check used by Chew et al [22]. With the method, the direct demand between departure and destination stations can be met, but more vehicles on the network will be needed [38].…”
Section: Generation Of Initial Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the routes are generated based on the shortest paths searching between OD pairs, and another procedure dealing with constraints is usually needed. For example, the construction and repair procedures used by Ahmed et al [35] and Szeto and Jiang [36], the initial solution generation procedure based on greedy algorithm used by Nikolić and Teodorović [24] and Nayeem et al [37], and the Floyd's algorithm and feasibility check used by Chew et al [22]. With the method, the direct demand between departure and destination stations can be met, but more vehicles on the network will be needed [38].…”
Section: Generation Of Initial Populationsmentioning
confidence: 99%
“…Firstly, the -shortest path search method in nonweighted road network is used to get the top paths between two endpoints of a line. All the top paths should meet the constraint about nodes number which can be expressed by the distance between the two endpoints of each path, as shown in Equation (35).…”
Section: Demand Assignmentmentioning
confidence: 99%
“…A new field of hyper-heuristic methods embedding data science techniques has recently been developed (Asta andÖzcan, 2015). Experiments on a hyper-heuristic benchmark framework (Kheiri and Keedwell, 2015), urban transit route design problem (Ahmed et al, 2019), wind farm layout optimization problem (Wilson et al, 2018), high school timetabling problem (Kheiri and Keedwell, 2017) and on water distribution optimization problem (Kheiri et al, 2015) have shown that applying a sequence of low level heuristics can potentially improve the quality of solutions more than those that simply select and apply a single low level heuristic.…”
Section: A Sequence-based Selection Hyper-heuristic (Team: Akhe)mentioning
confidence: 99%
“…A prominent example is the instance published by Mandl (1979) [used e.g. in Ahmed et al (2019), Arbex and da Cunha (2015) Baaj and Mahmassani (1991), Fan and Mumford (2010) and Nayeem et al (2014)]. Another often used test instance [e.g.…”
Section: Introductionmentioning
confidence: 99%